Oncolytic Viral Therapy and the Immune System: A Double-Edged Sword Against Cancer - Marelli, Giulia; Howells, Anwen; Lemoine, Nicholas R.; Wang, Yaohe (Frontiers in Immunology, 2018)
Oncolytic viral therapy is a new promising strategy against cancer. Oncolytic viruses (OVs) can replicate in cancer cells but not in normal cells, leading to lysis of the tumor mass. Beside this primary effect, OVs can also stimulate the immune system. Tumors are an immuno-suppressive environment in which the immune system is silenced in order to avoid the immune response against cancer cells. The delivery of oncolytic viruses into the tumor wakes up the immune system so that it can facilitate a strong and durable response against the tumor itself. Both innate and adaptive immune responses contribute to this process, producing an immune response against tumor antigens and facilitating immunological memory. However, viruses are recognized by the immune system as pathogens and the consequent anti-viral response could represent a big hurdle for OVs. Finding a balance between anti-tumor and anti-viral immunity is, under this new light, a priority for researchers. In this review, we provide an overview of the various ways in which different components of the immune system can be allied with OVs. We have analysed the different immune responses in order to highlight the new and promising perspectives leading to increased anti-tumor response and decreased immune reaction to the oncolytic viruses.